ANTIDIABETIC DRUGS UTILIZATION PATTERNS IN A NIGERIAN TERTIARY HEALTHCARE FACILITY - S, ALIYU; H.I, MAHMUD; BELLO, F; M.A., ZAYYAD (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2021)
Worldwide, diabetes mellitus (DM) is considered a public health care problem. Studies have shown that DM is on an alarming rise in Nigeria, and antidiabetic medications are the mainstay for its management. Rational use of antidiabetics is important in achieving desired therapeutic outcomes. Therefore, this study aimed at assessing antidiabetic drug utilization patterns at the Medical Out-Patients Department (MOPD) of Ahmadu Bello University Teaching Hospital (ABUTH). A prospective, cross-sectional study design was used for data collection on a sample of 603 patients who attended the facility between 8th June and 28th September 2015. Data were collected according to the World Health Organization (WHO) method for drug utilization studies. The results showed that an average of 1.8 antidiabetics was observed per prescription. Oral antidiabetic drugs (OADs) (with 6.045 Defined Daily Dose, DDD/1000 patients/day) were 49.55 times more utilized than insulin (with 0.122 DDD/1000 patients/day). Metformin, with 4.358 DDD/1000 patients/day was the most utilized OAD. The cost/DDD within the DU90% segment was NGN 1,786.46 (US$8.97). In conclusion, metformin was the most utilized antidiabetic and the costs of antidiabetics were high in the facility. It is therefore recommended that interventions to curtail the cost of drugs in the facility should be adopted.